United Republic of Tanzania : Financial System Stability Assessment Update. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The global recession has had a significant impact on economic performance and the outlook in Tanzania. Tanzanian banks were not directly affected by the global financial crisis, but second-round effects of the crisis have intensified the risks to the financial sector. Domestic liquidity tightened considerably at the onset of the global financial crisis but has since eased, owing to a significant loosening of monetary policy to help mitigate the economic downturn. The policy response of the authorities included a rescue package designed to support sectors affected by the crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet